Modeling Simulation and Design of Photovoltaic Array with MPPT Control Techniques - Sangita Ramesh Nandurkar; Mini Rajeev (Institute of Advanced Engineering and Science, 2014)
The Renewable energy is important part of power generation system due to diminution of fossils fuel. Energy production from photovoltaic (PV) is widely accepted as it is clean, available in abundance, & free of cost. This paper deals with modeling of PV array including the effects of temperature and irradiation. The DC-DC converter is used for boosting low voltage of the PV array to high DC voltage. Since the efficiency of a PV array is around 13% which is low, it is desirable to operate the module at the peak power point to improve the utilization of the PV array. A maximum power point tracker (MPPT) is used for extracting the maximum power from the solar PV array and transferring that power to the load. To track maximum power point (MPP) Perturb & Observe (P & O) algorithm is used which periodically perturbs the array voltage or current and compare PV output power with that of previous perturbation cycle which controls duty cycle of DC-DC converter. The entire system is simulated in MATLAB /SIMULINK and simulation results are presented.